The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/bs11080105
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitudes, and Practices Regarding Dengue among Physicians: A Web-Based Cross-Sectional Survey

Abstract: Dengue fever is one of the most important viral infections transmitted by Aedes mosquitoes and a major cause of morbidity and mortality globally. Accurate identification of cases and treatment of dengue patients at the early stages can reduce medical complications and dengue mortality rate. This survey aims to determine the knowledge, attitude, and practices (KAP) among physicians in dengue diagnosis and treatment. This study was conducted among physicians in Turkey as one nonendemic country and Bangladesh, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
1
5
0
3
Order By: Relevance
“…In a similar study, general practitioners in Indonesia knew relatively little about the emerging infection known as monkeypox [13] , [14] . In contrast, regarding endemic diseases in Bangladesh, the level of knowledge is rather high; most doctors are well-versed in diseases such as "dengue," which are transmitted by Aedes aegypti [18] . It should not come as a surprise that participants in general lack awareness about monkeypox since it is a re-emerging infectious disease, and instances of it have never been documented in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, general practitioners in Indonesia knew relatively little about the emerging infection known as monkeypox [13] , [14] . In contrast, regarding endemic diseases in Bangladesh, the level of knowledge is rather high; most doctors are well-versed in diseases such as "dengue," which are transmitted by Aedes aegypti [18] . It should not come as a surprise that participants in general lack awareness about monkeypox since it is a re-emerging infectious disease, and instances of it have never been documented in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania, Saringe et al (Saringe et al, 2019) found that 74.1% of healthcare workers possessed good dengue knowledge, with a mean score of 43.6 (considered good if ≥ 40). Additionally, a multi-country study revealed that Bangladesh, India, and Malaysia had the highest dengue knowledge scores (16.9, 18.03, and 18.46, respectively), while Turkey scored lower (11.7) (Koonisetty et al, 2021). These studies suggest that the good knowledge could be due to the constant dengue cases presented in those areas, a situation similar to Peru.…”
Section: Discussionmentioning
confidence: 90%
“…al., 2021;Koonisetty et al, 2021;Tomashek et al, 2014). However, this study divided respondents according to macroregions within the same country, and despite the fact that the Eastern macroregion tends to have the highest number of cases and is considered a dengue endemic area (Ministerio de Salud del Perú, 2023g), in the multivariable analysis, living in this macroregion was negatively associated with obtaining a score ≥ 70%.…”
mentioning
confidence: 96%
“…Besides, the WHO Strategic Advisory Panel has recommended the use of Dengvaxia® for dengue-seropositive patients only because it has been found to increase the risk of severe dengue in seronegative individuals [5], [6]. To date, dengue treatment has relied on the management of clinical signs and symptoms, including the prescription of non-steroidal anti-inflammatory agents (NSAIDs), clinical parameters tracking, and fluid management to stabilise hemodynamic status [7]. Currently, there is still no specific treatment for dengue [2], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…To date, dengue treatment has relied on the management of clinical signs and symptoms, including the prescription of non-steroidal anti-inflammatory agents (NSAIDs), clinical parameters tracking, and fluid management to stabilise hemodynamic status [7]. Currently, there is still no specific treatment for dengue [2], [7], [8]. Although some drugs such as chloroquine, balapiravir, and lovastatin are being tested in human clinical trials to treat dengue at different stages of development, these drugs have not been approved yet for use against dengue [9], [10].…”
Section: Introductionmentioning
confidence: 99%